CELIAC DISEASE- INFLUENCE ON FERTILITY, PREGNANCY COURSE, POSTNATAL OUTCOMES - LITERATURE REVIEW - Warzocha-Żurek, Daria Aleksandra; Szwed, Agnieszka; Ziemba-Furgała, Natalia Matylda; Borzęcka, Katarzyna Anna; Wawrzonek, Katarzyna; Andryszko, Krystian; Polewczak-Karp, Ewa Maria; Sołtys, Aleksandra; Krysa, Paulina; Dymon, Marcelina (International Journal of Innovative Technologies in Social Science, 2026)
Celiac disease is a systemic autoimmune disease caused by the ingestion of gluten in genetically predisposed individuals and is considered a significant but not well-recognized cause of female reproductive health problems. In this paper, a literature review of the medical literature from PubMed/MedLine, Google Scholar, and Cochrane databases was conducted to identify literature on the relationship between celiac disease and fertility, pregnancy outcomes, and birth outcomes. The medical literature appears to indicate that untreated or undiagnosed celiac disease may contribute to problems of delayed conception, unexplained infertility, recurrent miscarriage, and other problems of disturbed reproductive health. Where the problem lies, is that there is a lack of early recognition of celiac disease in adults because of nonspecific presenting symptoms. In addition, active disease during pregnancy has been associated with adverse pregnancy and birth outcomes, including intrauterine growth retardation, low birth weight, small for gestational age babies, preterm birth, and even death of the baby. Often problems of conception are the first symptom of celiac disease. Evidence also suggests that adherence to a glutenfree diet may greatly mitigate these risks and improve reproductive and perinatal outcomes. Increased awareness of celiac disease among women presenting with unexplained infertility or poor pregnancy history may lead to early diagnosis and effective management of the disease. A good course of action for the future, would be to compile a list of people in each country, with celiac disease who could support one another.